A variation on forced migration: Wilhelm Peters (Prussia via Britain to Turkey) and Muzafer Sherif (Turkey to the United States). Issue 3 (2nd July 2016) - Russell, Gül
ABSTRACT: In 1933 the Turkish Republic formally offered university positions to 30 German-speaking academics who were dismissed with the coming to power of the National Socialist Government. That initial number went up to 56 with the inclusion of the technical assistants. By 1948 the estimated total had increased to 199. Given renewable five-year contracts with salaries substantially higher than their Turkish counterparts, the foreign émigrés were to implement the westernization program of higher education. The ten year-old secular Turkish Republic's extensive social reforms had encompassed the adoption of the Latin alphabet, and equal rights for women, removing gender bias in hiring. Such a high concentration of émigré academics in one institution, "the highest anywhere in the world, " provides a unique opportunity to study a subject which has been neglected. In this article two cases in psychology will be examined: Wilhelm Peters (1880–1963), who came, via Britain, to Istanbul in 1936 from the University of Jena in Germany, and Muzafer Sherif (1906–1988) who went to the United States from Ankara University in 1945. The purpose of the comparative analysis is to identify the features that are specific to the German experience, and those that are shared and underlie translocation in science within the multifaceted complexity of the process of forced migration.